Upaya Meningkatkan Kompetensi Guru Dalam Menyusun Media Pembelajaran Berbasis Multimedia Interaktif Melalui Lesson Study di SDN 41/X Sungai Jambat Pada Semester Ganjil Tahun Ajaran 2021/2022 - Pasman Pasman (Departement of Mathematics Education, 2023)
This study aims to obtain information and discuss efforts to increase teacher competency in developing interactive multimedia-based learning media through lesson study at SDN 41/X Sungai Jambat in the odd semester of the 2021/2022 school year. This research is a school action research (PTS) which consists of two cycles by following the four stages of planning, implementing, observing and reflecting. This research was conducted at SDN 41/X Sungai Jambat in the odd semester of the 2021/2022 school year with a total of 5 teacher subjects. Data was collected through observation sheets and documentation and analyzed using proportions and data reduction. Based on the results of the research and discussion, it can be interpreted that through lesson study it can increase teacher competency in compiling interactive multimedia-based learning media at SDN 41/X Sungai Jambat in the odd semester of the 2021/2022 school year. Classically, almost all teachers have good professional competence after lesson study.